Research on the Attenuation Characteristics of LiDAR Transmission Energy in Different Atmospheric Environments - Xiaoce Yang; Chunyang Wang; Xuelian Liu (Atmosphere)
LiDAR, as a novel detection system, has found extensive applications across diverse industries. However, when lasers propagate through the atmosphere, the energy undergoes significant attenuation due to various environmental factors, thereby impeding the performance of LiDAR systems. This paper focuses on analyzing the distribution patterns of fog particles, haze particles, and typical aerosol particles within the atmospheric environment. By integrating Mie scattering theory, it delves into the absorption and scattering behaviors exhibited by different atmospheric constituents. Employing numerical simulation techniques, the attenuation characteristics of the 1064 nm working-wavelength laser under the influence of diverse particles are simulated and scrutinized. In conjunction with the LiDAR transmission equation, the attenuation law governing the transmission energy of the laser under varying atmospheric conditions is also analyzed. The results reveal that atmospheric pollutant particles such as fog particles, haze particles, dust particles, and bituminous coal particles all contribute to energy attenuation during laser transmission. Notably, bituminous coal particles induce the most severe attenuation.